Índice de Conformidade ao Enquadramento relacionado às fragilidades ambientais no entorno do reservatório de uma Pequena Central Hidrelétrica no nordeste paranaense - Amaral, Camila Zeni do (2024)
Electricity generated by hydropower plants plays a crucial role in Brazil's energy matrix. The increasing electricity consumption, driven by social development, demands an expansion of energy generation to meet the growing demand and achieve the Sustainable Development Goals (SDGs). However, the implementation of new hydropower generation units — including Hydropower Plants, Small Hydropower Plants (SHPs), or Large Hydropower Plants — can generate externalities that significantly impact local communities and the environment.In this context, the present study evaluated the Conformity to Framework Index (ICE) as a tool to measure the gap between water quality and legally established standards. The research analyzed the relationship between land-use changes, environmental vulnerabilities, and the preservation of Permanent Preservation Areas (APPs) surrounding the reservoir of an SHP located in northeastern Paraná state. Using geoprocessing techniques, data on slope, soil types, and land use were assessed, enabling the identification of emerging environmental vulnerabilities in the study area. The results indicate that the region does not present critical environmental vulnerability points, with 51.5% of the area occupied by forest use, including APPs and areas designated for pine and eucalyptus plantations. The analysis shows that the APPs surrounding the reservoir comply with Federal Law No. 12,651/2012 (New Forest Code). The ICE calculation revealed that water quality, both upstream and downstream of the reservoir, is classified as excellent, fully meeting the legal limits for the evaluated parameters. The analyses, which encompass emerging environmental vulnerabilities, APP assessment, and ICE application, demonstrate that the area surrounding the SHP reservoir exhibits high environmental compliance. Furthermore, the findings highlight that APPs play a crucial role in preserving water quality, contributing to environmental sustainability and compliance with legal requirements..